Analysis of Development Strategy for Conservation Area of Leatherback Turtle (Dermochelys coriacea) in Wermon Coast of Tamrauw Regency - Baru, Habel; Kasnir, Muh.; Jayadi, Jayadi (AgriSains, 2019)
This research aimed to identify factors threatening the population and migration of leatherback turtles, analyze community perceptions (stakeholders) from ecological, economic, cultural, legal and institutional aspects, formulate policy strategy of management and development of leatherback turtle conservation area on the Wermon Coast of Tambraw Regency. Data collection techniques used were literature study and field studies through interviews, observation and documentation. Sampling was conducted by purposive sampling method with the number of respondents of 50 persons. The results showed that several factors that threatened the population and migration of leatherback turtles were sand temperature and temperature variations, sea level rise, beach slope, and sand texture. Community perception of ecological aspects showed 80% positive habits, economic aspect increased local people's income, cultural aspect showed 90% of respondents accept, legal and institutional perceptions showed 94% of people support spatial planning policies and 86% social institutions support the development of conservation areas. Several SWOT analysis strategies for developing leatherback turtle conservation area, namely provide training for management of leatherback turtle conservation, create a community-based turtle conservation management manuals, improve facilities and infrastructure, increase monitoring of coral reef resources, implements strict control of pollution materials that can disrupt the living conditions of leatherback turtles, increase public understanding of conservation areas and promote the role of the leatherback turtle in the community.Keywords: Conservation area, leatherback turtle, SWOT analysis.